Evaluasi Konsep Value for Money terhadap Penilaian Kinerja Pelayanan Sektor Publik - Mutiya Krisanty; Maya Widyana Dewi; M. Hasan Ma’ruf (Nur Science Institute, 2022)
This study aims to determine the effect of efficiency and effectiveness on the performance of public sector services of the Gadingan Village Government in 2020. This research is quantitative. A sample of 100 respondents. Data collection techniques through surveys by distributing questionnaires to respondents to be targeted. Data analysis methods include descriptive statistical analysis, validity, reliability, and classical assumption tests. The results showed that 1) economic elements, efficiency, and effectiveness simultaneously as elements of value for money affect the performance of public sector services, 2) economic elements partially as one of the elements of value for money affect the performance of public sector services in the Gadingan Village Head's Office, 3) the element of efficiency partially as one of the elements of value for money affects the performance of public sector services in the Village Head's Office Gadingan, and 4) the element of partial effectiveness as one of the elements of value for money affects the performance of public sector services in the Gadingan Village Head's Office